ECONOMIC ASPECTS OF ACCESSIBILITY DESIGN IN HOSPITALITY FOR SUSTAINABLE DEVELOPMENT - Іщенко, Н.; Дроботова, М.; Музичка, А.Р. (SWorldJournal, 2025)
The article examines the economic aspects of accessibility design in the hospitality industry as a key factor of sustainable development. Accessibility is considered not only as a social necessity but also as an economically beneficial investment for hot